Prinsip Kepribadian Individual Tokoh Akashi Karya Fujimaki Tadatoshi Melalui Alfred Adler - Karina Sekar Ramadhani; Hendri Zuliastutik (Janaru Saja Jurnal Program Studi Sastra Jepang, 2024)
Abstract The study, titled "Personality Principles of Akashi Characters by Alfred Adler", was conducted because researchers became interested in the individuality of Akashi characters. Akashi is the son of a respected family who grew up with love and discipline, so Akashi has an excellent personality, a personality and a strict lifestyle that makes someone want to be strong, a lifestyle that makes people want to be strong. goal. Against the background of the above problems, the purpose of this research is to clarify the principle that forms the personality of Akashi in the anime "Kuroko's Basketball" by Tadatoshi Fujimaki. Researchers use the Individual Psychological Approach of Alfred in his Adler Individual Psychology. This study uses a qualitative method with descriptive data analysis. The data source for this study is Season 3 of Kuroko's Basketball anime by Tadatoshi Fujimaki. As a result of this research, the individual personality includes her six principles: struggle for success or superiority, subjective observation, unity of personality, social concern, lifestyle and self-creativity, and the status of an only child. It was shown that there is The principles that most influence an individual's character development are the struggle for success or dominance and lifestyle. The above results show that the personal character principles that most affect Akashi's character are his struggle for superiority and his lifestyle. Keywords: Akashi, Alfred Adler, Individual Personality Abstrak Kajian “Prinsip Kepribadian Individual Tokoh Akashi Melalui Alfred Adler” ini dilakukan karena peneliti tertarik dengan kepribadian individual dari karakter Akashi. Akashi adalah anak dari keluarga terpandang yang tumbuh dengan cinta dan disiplin, sehingga Akashi memiliki kepribadian yang luar biasa, kepribadian yang membuat seseorang ingin menjadi kuat dan memiliki gaya hidup yang keras, gaya hidup yang membuat orang ingin menjadi kuat untuk mencapai tujuannya. Sasaran berdasarkan permasalahan di atas, maka tujuan dari penelitian ini adalah untuk mendeskripsikan prinsip-prinsip pembentuk kepribadian Akashi dalam anime Kuroko no Basuke karya Fujimaki Tadatoshi. Peneliti menggunakan teori Psikologi Kepribadian Individu Alfred Adler. Penelitian ini menggunakan metode kualitatif dengan analisis data deskriptif. Sumber data penelitian ini adalah anime Fujimaki Tadatoshi Kuroko no Basuke Season 3. Hasil penelitian ini menunjukkan bahwa kepribadian individu memiliki 6 prinsip yaitu, perjuangan untuk sukses atau superioritas, observasi subjektif, kesatuan kepribadian, kepentingan sosial, dan gaya hidup. dan kekuatan kreatif diri dan status anak tunggal. Prinsip yang paling mempengaruhi kepribadian seseorang adalah perjuangan untuk sukses atau superioritas dan gaya hidup. Hasil di atas menunjukkan bahwa prinsip kepribadian individu yang paling mempengaruhi karakter Akashi adalah perjuangan untuk supremasi dan cara hidup. Kata kunci: Akashi, Alfred Adler, Kepribadian Individual